Do local causations matter? The effect of firm location on the relations of ROE, R&D, and firm SIZE with MARKET-TO-BOOK - Carosi, Andrea (Journal of Corporate Finance, 2016)
Firm location affects the relations of ROE, R&D, and firm SIZE with MARKET-TO-BOOK. Local parameters that are specific to the firm geographic location are estimated by weighting observations in function of their proximity. The local effect of ROE increases with the earnings quality of the neighboring firms, which is consistent with the local sharing of the accounting practices. According to value-enhancing spillover of knowledge among nearby firms, the effect of R&D is boosted by within-region R&D. Finally, the small-size effect weakens with the firm isolation, which supports the superior information of local investors. Firm location endogeneity is addressed focusing on firms operating in different industries where endogenous similarities are highly unlikely, and findings remain unchanged. Local factors shape relationships of causations and enhance effects that vary firm the firm location. Overall, local causations matter.